Photocurrent-induced harmonics in nanostructures - Babushkin Ihar; Husakou Anton; Shi Liping; Demircan Ayhan; Kovacev Milutin; Morgner Uwe (Nanophotonics)
Photocurrent-induced harmonics appear in gases and solids due to tunnel ionization of electrons in strong fields and subsequent acceleration. In contrast to three-step harmonic emission, no return to the parent ions is necessary. Here we show that the same mechanism produces harmonics in metallic nanostructures in strong fields. Furthermore, we demonstrate how strong local field gradient, appearing as a consequence of the field enhancement, affects photocurrent-induced harmonics. This influence can shed light at the state of electron as it appears in the continuum, in particular, to its initial velocity.